Collected Works of C. G. Jung, Volume 5 : Symbols of Transformation - Jung, C. G. (Carl Gustav), 1875-1961 (Book collections on Project MUSE., 1967)
A complete revision of Psychology of the Unconscious (orig. 1911-12), Jung's first important statement of his independent position.